EFFECTIVENESS OF PINE SAP COLLECTING TOOLS BASED ON SIEVER VARIATION IN IMPROVING THE QUALITY OF PINE SAP HARVESTING - Jumini, Sri; Abdul Hanan, Ishaq; Khotimah, Khusnul; Arsyad, Muaddiul; Indratama, Andin (BRIN Publishing, 2025)
Perhutani continues to improve the quality of pine sap harvest through the coakan method and the innovation of containers right under the sap drips. However, the quality produced is still less than optimal. Based on this, a pine sap container based on a filter was made that can improve the quality of the harvested pine sap. This study aims to determine the effectiveness of the pine sap container based on variations in filters and inclined planes on the tapping gutter. The study was conducted using an experimental method to obtain the mechanical advantage parameters of an economical pine sap container that can increase the productivity of the tool's performance based on the concept of an inclined plane. Testing was carried out in the laboratory to design and measure the mechanical efficiency of the tool, and field observations were continued to evaluate the quality and productivity of the pine sap produced. Data collection was carried out by systematically measuring the mass of sap, the angle of inclination of the gutter, and the mechanical parameters of the tool. The experiment showed that the largest mechanical advantage parameter value was found in the tapping gutter with the largest angle of inclination, namely 70°. In addition, this tool, with an innovative filter-based design and optimal angle of inclination, has been proven to improve the sap quality and minimize dirt and water pollution. The results of this study indicate that the developed tool is effective in increasing the efficiency of harvesting and the quality of pine sap, which is in line with the research objective to optimize the process of collecting pine sap. The tool produced by the researcher is a semicircular bowl-shaped container equipped a lid that can prevent dirt and rainwater from entering so that good-quality sap is obtained. This tool can improve the quality of sap with a higher purity level while producing harvesting efficiency of up to 25% compared to traditional methods, so this innovation has the potential to be an effective solution to increase the productivity of pine sap harvests sustainably.